Knowledge and human interests - Habermas, Jürgen (Social theory., 1987)
Habermas describes Knowledge and Human Interests as an attempt to reconstruct the prehistory of modern positivism with the intention of analysing the connections between knowledge and human interests. Convinced of the increasing historical and social importance of the natural and behavioural sciences, Habermas makes clear how crucial it is to understand the central meanings and justifications of these sciences. He argues that for too long the relationship between philosophy and science has been distorted. In this extraordinarily wide--ranging book, Habermas examines the principal positions of modern philosophy -- Kantianism, Marxism, positivism, pragmatism, hermeneutics, the philosophy of science, linguistic philosophy and phenomenology -- to lay bare the structure of the processes of enquiry that determine the meaning and the validity of all our statements which claim objectivity. This edition contains a postscript written by Habermas for the second German edition of Knowledge and Human Interests.